2022
DOI: 10.1080/19490976.2022.2107386
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to discern if microbiome associations reflect causation in metabolic and immune disorders

Abstract: Our understanding of microorganisms residing within our gut and their roles in the host metabolism and immunity advanced greatly over the past 20 years. Currently, microbiome studies are shifting from association and correlation studies to studies demonstrating causality of identified microbiome signatures and identification of molecular mechanisms underlying these interactions. This transformation is crucial for the efficient translation into clinical application and development of targeted strategies to bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…This is also envisioned by a new approach for specific depletion of well selected bacterial species in the human GM [7]. The strict use of highly standardized GFmodels or gnotobiotic models appears more promising in this than the "simple" depletion and modification of the GM by systemic antibiosis [179].…”
Section: Discussionmentioning
confidence: 99%
“…This is also envisioned by a new approach for specific depletion of well selected bacterial species in the human GM [7]. The strict use of highly standardized GFmodels or gnotobiotic models appears more promising in this than the "simple" depletion and modification of the GM by systemic antibiosis [179].…”
Section: Discussionmentioning
confidence: 99%
“…Finding that gut microbiota plays a direct role in promoting adipose inflammation, Caesar and colleagues reported that germ-free mice reduced macrophage accumulation in adipose tissue and improved glucose metabolism compared to their conventionally engineered counterparts [15]. Although the causal role of gut microbiota has generally been studied in animal models, cross-sectional studies have identified microbiota profiles associated with metabolic diseases in humans [16]. In this sense, recent studies support the role of dysbiotic alterations in metabolic diseases such as obesity [17] and T2D [18] and suggest that the gut microbiota may be a novel therapeutic target for the amelioration of T2D and related diseases [18].…”
Section: Obesity and Gut Microbiota Relationshipmentioning
confidence: 99%
“…Compared with conventional mice, germ-free mice display profound immune defects and impaired growth [39 ▪ ]. Moreover, in mouse models for obesity, inflammatory bowel disease and asthma, germ-free mice develop the disease phenotype after receiving stool transplantation from diseased mice, with some evidence of clinical improvement following microbial restoration [40 ▪ ]. Antibiotics can induce or worsen a pathological phenotype in mice (such as allergic sensitization [41 ▪ ] or experimentally induced colitis [42]).…”
Section: Association Causation and Future Directionsmentioning
confidence: 99%